Challenges facing implementation of Zanzibar education policy in the area of Teachers’ on-the-job training: The case of North ‘A’ District Zanzibar. - Kombo, Khamis S. (Mzumbe University, 2024)
A dissertation submitted to Institute of Development study in partial/ fulfillment of the requirements for the Degree of Master of Science in Development Policy (MSc. DP) of Mzumbe University